ANALYSIS OF CONFLICT IN A MISFORTUNE BY ANTON CHEKHOV - Dwi Uswatun Khasanah (Universitas Bengkulu, 2021)
This paper aims to find the conflict that exists in the story of A Misfortune by Anton Chekhov. This research method is descriptive analytical research methods. The data collection technique of this study uses documentary techniques sourced from the stories of A Misfortune by Anton Chekhov. The conflict found by researchers in the form of sentences, phrases and word quotations. Based on the analysis carried out, the researchers also found two types of conflicts, namely people vs. self and people vs. people. The first, the main character who has a conflict with himself such as feelings of doubt, confusion, anger, chaos, sadness, despair, shock, fear, regret, revenge, and annoyance. Second, the main character has problem with other character figures such as quarrels, debates, disagreements, and disputes.